Relationship Between Motivation, Competence, Workload, and Nurse Performance, at Dr. Soediran Mangun Sumarso Hospital, Wonogiri, Indonesia - Agus Sutarto; Hermanu Joebagio; Pawito - (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Health worker performance is one of the key elements that determine the quality of hospital service. Health worker performance therefore is the target forimprovement. This study aimed to analyze the relationship between motivation, competence, workload of nurses, and nurse performance.Subjects and Method: This was an analytical observational study with cross sectional design. This study was conducted at Dr. Soediran Mangun Sumarso Hospital, Wonogiri, Indonesia. A total of 50 nurses was sampled for this study.The independent variables consisted of motivation, competence, and workload. The dependent variable was performance of nurse. The data were collected by a questionnaire and analyzed by multiple linear regression model.Results: This study did not find relationship between motivation and performance of nurse (b = 0.02; 95% CI=-0.19 to 0.24; p= 0.823). Similarly there was no relationship workload and performance of nurse (b=0.05; 95% CI= -0.15 to 0.26; p = 0.607). There was a positive and statististically significant relationship between competence and performance of nurse (b = 1.10; 95% CI= 1.75 to 0.46; p= 0.001).Conclusion: There is a positive and statistically significant relationship between competence and performance of nurse.Keywords: motivation, competence, workload, performance, nurseCorrespondence: Agus Sutarto. dr. Soediran Mangun Sumarso Hospital, Wonogiri, East Java. Email: agus_skh70@yahoo.co.idJournal of Health Policy and Management (2016), 1(2): 78-94https://doi.org/10.26911/thejhpm.2016.01.02.03